Development and use of an atomistic CHARMM‐based forcefield for peptoid simulation. Issue 5 (29th November 2013) - Mirijanian, Dina T.; Mannige, Ranjan V.; Zuckermann, Ronald N.; Whitelam, Stephen
<x xml:space="preserve">Abstract</x> Peptoids are positional isomers of peptides: peptoid sidechains are attached to backbone nitrogens rather than α‐carbons. Peptoids constitute a class of sequence‐specific polymers resistant to biological degradation and potentially as diverse, structurally and functionally, as proteins. While molecular simulation of proteins is commonplace, relatively few tools are available for peptoid simulation. Here, we present a first‐generation atomistic forcefield for peptoids. Our forcefield is based on the peptide forcefield CHARMM22, with key parameters tuned to match both experimental data and quantum mechanical calculations for two model peptoids (dimethylacetamide and a sarcosine dipeptoid). We used this forcefield to demonstrate that solvation of a dipeptoid substantially modifies the conformations it can access. We also simulated a crystal structure of a peptoid homotrimer, H‐(N‐2‐phenylethyl glycine)3‐OH, and we show that experimentally observed structural and dynamical features of the crystal are accurately described by our forcefield. The forcefield presented here provides a starting point for future development of peptoid‐specific simulation methods within CHARMM. © 2013 Wiley Periodicals, Inc.